Anti-heparanase activity of ultra-low-molecular-weight heparin produced by physicochemical depolymerization. (1st January 2016) - Achour, Oussama; Poupard, Nicolas; Bridiau, Nicolas; Bordenave Juchereau, Stephanie; Sannier, Fredéric; Piot, Jean-Marie; Fruitier Arnaudin, Ingrid; Maugard, Thierry
Highlights: Production of ultrasonic Ultra Low Molecular Weight Heparin (usULMWH). Innovative ultrasonic assisted radical depolymerization of heparin produced usULMWH. usULMWH structure and biological activities were compared to others heparins. usULMWH have high anti-heparanase activity and moderate anticoagulant activities. usULMWH might be potential anti-angiogenic candidates for cancer therapy. Abstract: Heparanase is an endo-β-D-glucuronidase that plays an important role in cancer progression, in particular during tumor angiogenesis and metastasis. Inhibiting this enzyme is considered as one of the most promising approaches in cancer therapy. Heparin is a complex glycoaminoglycan known as a strong inhibitor of heparanase. It is primarily used in clinical practice for its anticoagulant activities, which may not be compatible with its use as anti-angiogenic agent. In this study, we described the production of ultra-low-molecular-weight heparins (ULMWH) by a physicochemical method that consists in a hydrogen peroxide-catalyzed radical hydrolysis assisted by ultrasonic waves. We assessed the structural characteristics, anticoagulant and anti-heparanase activities of the obtained heparin derivatives and compared them with three commercial low-molecular-weight heparins (LMWH), glycol-split non-anticoagulant heparins and heparins produced by enzymatic methods. ULMWH generated by the physicochemical method were characterized by high anti-heparanase and moderate anticoagulant activities. These heparin derivatives might be potential candidates for cancer therapy when a compromise is needed between anti-heparanase and anticoagulant activities.